Rapid actin‐cytoskeleton–dependent recruitment of plasma membrane–derived dysferlin at wounds is critical for muscle membrane repair. Issue 8 (1st May 2014) - McDade, Joel R.; Archambeau, Ashley; Michele, Daniel E.
Abstract : Deficits in membrane repair may contribute to disease progression in dysferlin‐deficient muscular dystrophy. Dysferlin, a type‐II transmembrane phospholipid‐binding protein, is hypothesized to regulate fusion of repair vesicles with the sarcolemma to facilitate membrane repair, but the dysferlin‐containing compartments involved in membrane repair and the mechanism by which these compartments contribute to resealing are unclear. A dysferlin‐pHluorin [dysf‐pH‐sensitive green fluorescent protein (pHGFP)] muscle‐specific transgenic mouse was developed to examine the dynamic behavior and subcellular localization of dysferlin during membrane repair in adult skeletal muscle fibers. Live‐cell confocal microscopy of uninjured adult dysf‐pHGFP muscle fibers revealed that dysferlin is highly enriched in the sarcolemma and transverse tubules. Laser‐wounding induced rapid recruitment of ~30 μm of local dysferlin‐containing sarcolemma, leading to formation of stable dysferlin accumulations surrounding lesions, endocytosis of dysferlin, and formation of large cytoplasmic vesicles from distal regions of the fiber. Disruption of the actin cytoskeleton decreased recruitment of sarcolemma‐derived dysferlin to lesions in dysf‐pHGFP fibers without affecting endocytosis and impaired membrane resealing in wild‐type fibers, similar to findings in dysferlin deficiency (a 2‐fold increase in FM1‐43 uptake). Our data support a new mechanism whereby recruitment of sarcolemma‐derived dysferlin creates an active zone of high lipid‐binding activity at wounds to interact with repair vesicles and facilitate membrane resealing in skeletal muscle.—McDade, J. R., Archambeau, A., Michele, D. E. Rapid actin‐cytoskeleton‐dependent recruitment of plasma membrane‐derived dysferlin at wounds is critical for muscle membrane repair. FASEB J. 28, 3660–3670 (2014). www.fasebj.org